2014
DOI: 10.1002/smll.201401658
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence of Gold Nanoclusters Composed of HAuCl4 and Histidine by Glutathione: Glutathione Detection and Selective Cancer Cell Imaging

Abstract: Glutathione (GSH) can significantly and selectively enhance the fluorescence intensity of Au nanoclusters (NCs) prepared by blending HAuCl4 and histidine in solution. The quantum yield of the Au NCs after adding GSH can reach above 10%. Besides, GSH capping shifts the excitation peak of Au NCs from ultraviolet (386 nm) to visible light (414 nm) and improves the stability of the Au NCs. The cytotoxicities of the Au NCs with and without GSH for normal lung cells (ATII) and cancerous lung cells (A549) are evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(127 citation statements)
references
References 75 publications
4
122
1
Order By: Relevance
“…It was found that GSH could significantly and selectively enhance the photoluminescence intensity of histidine-stabilized Au clusters. 423 In the presence of GSH, the quantum yield of Au clusters could reach levels above 10% without other thiolate molecules impacting the photoluminescence. Based on this "turn on" strategy, a LOD of 0.2 μM was demonstrated for GSH in the detection range of 150−1200 μM.…”
Section: Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…It was found that GSH could significantly and selectively enhance the photoluminescence intensity of histidine-stabilized Au clusters. 423 In the presence of GSH, the quantum yield of Au clusters could reach levels above 10% without other thiolate molecules impacting the photoluminescence. Based on this "turn on" strategy, a LOD of 0.2 μM was demonstrated for GSH in the detection range of 150−1200 μM.…”
Section: Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…16-22 Glutathione (GSH) is an important antioxidant and the most abundant low-molecular weight thiol in vivo, with a concentration range from 1 to 15 mM. 23 At the same time, however, it has been shown to consume 1 O 2 generated by PDT agents, thus greatly reducing the efficiency of PDT and limiting the clinical applications of current PDT agents. 24-26 Therefore, the development of a multifunctional nanosystem which can both enhance the cellular uptake of photosensitizers and decrease the level of GSH in cancer cells in situ is highly desired.…”
mentioning
confidence: 99%
“…52 It is necessary to monitor level of glutathione due to its biological significance in diseaces such as cancer, 53 HIV 54 and heart problems. 55 SiPM were able to in situ reduce KMnO 4 to MnO 2 sheets by immersing SiPM in KMnO 4 aqueous solutions (here we used HD-SiPM).…”
Section: Resultsmentioning
confidence: 99%